Fibroblasts as therapeutic targets in rheumatoid arthritis and cancer (Swiss Medical Weekly, 2012)
Rheumatoid arthritis (RA) is a common chronic inflammatory disease that causes progressive synovial inflammation resulting in irreversible joint destruction, chronic disability and premature mortality [1, 2]. Although it is recognised that in RA, inflammation and its persistence result from complex interactions between haematopoietic and stromal cells [3–5], research into the pathogenesis of the disease has traditionally concentrated on cells and cytokines of the immune system, neglecting the role of stromal cells. As a consequence, new biologic treatments have been developed, which have led to a step-change in the management of the disease [6]. Nevertheless, these treatments do not reverse tissue damage or lead to disease cure and are not effective for all patients. Furthermore, at best they induce a significant clinical response (ACR70) in less than 60% of patients, most of whom will relapse on treatment withdrawal, suggesting that additional therapeutic targets, responsible for complete resolution of inflammation, remain to be discovered [7]. An increasing body of evidence implicates RA synovial fibroblasts in driving the persistent, destructive characteristics of the disease. In this paper, we discuss the evidence implicating synovial fibroblasts in the pathogenesis of RA and explore their role as therapeutic targets.